2019
DOI: 10.1111/jce.13928
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of lesion quality estimated by ablation index: An in vitro study

Abstract: Limitations of the ablation index background: Ablation index (AI) is a novel marker of lesion quality from radiofrequency (RF) catheter ablation. However, AI reliability has not been fully validated by experimental data. The aim of the present study is to validate AI reliability for estimating lesion size using different settings for RF parameters: contact angle, power delivery, and contact force (CF). Methods and results:We evaluated the lesion size in porcine hearts (N = 108) after RF application at three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 16 publications
1
54
0
Order By: Relevance
“…Bourier et al found larger but shallower lesions with similar lesion volumes, using HPSD in an in vitro model. In another in vitro study, Kawaji et al found an influence of power settings and contact angle on the obtained AI values. Interestingly, they found smaller lesion volumes with HPSD.…”
Section: Discussionmentioning
confidence: 94%
“…Bourier et al found larger but shallower lesions with similar lesion volumes, using HPSD in an in vitro model. In another in vitro study, Kawaji et al found an influence of power settings and contact angle on the obtained AI values. Interestingly, they found smaller lesion volumes with HPSD.…”
Section: Discussionmentioning
confidence: 94%
“…Only recently, Kawaji et al investigated the lesion quality in relation to different contact angles to the myocardium 18 . Using a Thermocool SmartTouch (Biosense‐Webster) catheter, the group found the ablation index, incorporating contact angle, power delivery, and CF settings to only poorly correlate with lesion size at higher contact angles.…”
Section: Discussionmentioning
confidence: 99%
“…tion to different contact angles to the myocardium. 18 Moreover, measures of CF can be used to predict gap formation after pulmonary vein isolation directly affecting recurrence rates of atrial fibrillation. 5,15 The maximal difference of lesion size between the surface aspect and the within-tissue aspect of the lesion has previously been shown to be 1-2 mm.…”
Section: Only Recently Kawaji Et Al Investigated the Lesion Quality mentioning
confidence: 99%
“…Values of AI may be the same between HPSD and conventional RF lesions, however, this is with respect only to the lesion volumes, as AI does not differentiate the lesion geometry (width and depth) . AI can vary depending on the catheter angles and the power delivered . The CLOSE protocol, adopted in the study by Berte et al, relies on AI as a guide for ablation (AI ≥ 400 at posterior segments and ≥ 550 at anterior segments, maximum inter‐lesion distance < 6 mm, and ablation line contiguity index >100%) .…”
Section: What Is the End‐point Of A Hpsd Lesion?mentioning
confidence: 99%
“…The authors themselves have exercised caution while using the routine values of AI in HPSD settings, especially while delivering lesions ≤ 4 seconds. It is also true that HPSD strategy may result in a lesser lesion depth at a set AI …”
Section: What Is the End‐point Of A Hpsd Lesion?mentioning
confidence: 99%